2015
DOI: 10.1111/jfs.12242
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Fresh Rainbow Trout by Sage Essential Oil and Packaging Treatments

Abstract: The present study aimed to investigate the effect of addition of sage oil in different packaging conditions on the quality of fresh trout fillets during storage at 4C. Six different treatments were tested: A; (without sage oil, air packaged), A1; (added sage oil 2% v/wt, air packaged), A2; (added sage oil 4% v/wt, air packaged), VP; (without sage oil, vacuum packaged), VP1 (added sage oil 2% v/wt, vacuum packaged) and VP2 (added sage oil 4% v/wt, vacuum packaged). The results indicated that total mesophilic ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Aksoy and Sezer [ 41 ] discovered that the combination of vacuum packaging and 2% laurel essential oil extended the shelf life of rainbow trout filets by approximately 4 days. Çoban et al [ 42 ] found that the combination of the vacuum packing and 2% sage essential oil resulted in an extension of the microbiological shelf life by 24 days and the combination of the vacuum packing and 4% sage essential oil by 34 days. In our study, the inhibitory effect of EOs against LAB in fish was limited to the first 5 days of storage; other EOs have different inhibitory activity against LAB.…”
Section: Discussionmentioning
confidence: 99%
“…Aksoy and Sezer [ 41 ] discovered that the combination of vacuum packaging and 2% laurel essential oil extended the shelf life of rainbow trout filets by approximately 4 days. Çoban et al [ 42 ] found that the combination of the vacuum packing and 2% sage essential oil resulted in an extension of the microbiological shelf life by 24 days and the combination of the vacuum packing and 4% sage essential oil by 34 days. In our study, the inhibitory effect of EOs against LAB in fish was limited to the first 5 days of storage; other EOs have different inhibitory activity against LAB.…”
Section: Discussionmentioning
confidence: 99%
“…177 These compounds have received substantial attention as useful natural antimicrobial agents. They exhibit a broad antimicrobial spectrum against different microorganisms 178 and possess sufficient heat stability to withstand incorporation into packaging materials. 23,179 Due to these multiple possibilities, each active packaging system needs to be adapted based on the food product, not only in terms of the materials used but also in terms of mechanism of release and action.…”
Section: Incorporation Of Essential Oils In the Matrixmentioning
confidence: 99%
“…-Plant extracts and essential oils. Aqueous or alcoholic extracts and essential oils from spices and vegetables such as cinnamon, allspice, clove, ginger, sage, eucalyptus, thyme, mustard, basil, rosemary, oregano, onion, garlic, lemon, horseradish, and others have been studied as antimicrobial agents (Çoban et al, 2016;Noshirvani et al, 2017;Ribeiro-Santos et al, 2017;Sirocchi et al, 2017;Mir et al, 2018;Bouarab Chibane et al, 2019), and were incorporated in chitosan-carboxymethyl cellulose, starch, gelatin, PLA, soy protein isolated, alginate, cellulose acetate films, and were proved to be effective as packaging of refrigerated beef meat, fresh rainbow, lard, chicken breast cuts, bologna and ham, etc. -Bacteriocins.…”
Section: Antimicrobialsmentioning
confidence: 99%